Bacterial Assessment of Selected Ready-To-Eat Foods Sold at Some Restaurants Within Federal Polytechnic Offa, Kwara State - Adeyinka E Ajiboye; Sheriffdeen O Alabi; Bukola A Hammed (UMYU Journal of Microbiology Research)
Foodborne illness can occur following the intake of food containing high number of viable bacteria and their toxins, although highly common and of public health concern, it is a very preventable occurrence. The research aimed at isolating and identifying the microorganisms that are present in ready to eat foods sold at the Federal Polytechnic, Offa, Kwara State, Nigeria and to study their antibiotics sensitivity patterns. A total of three (3) samples of ready to eat food (White Rice, Beans and Moin moin) were collected from three different canteens within the school premises. Standard methods were used for the total aerobic bacterial counts, coliform counts, Staphylococcus count and Salmonella-Shigella counts. Identification of isolates were performed using various biochemical tests and the antimicrobial sensitivity of bacterial isolates obtained from the food samples was also performed using disc diffusion assay. Beans sample has the highest total aerobic bacteria, Staphylococcus, Salmonella and Shigella counts of 26.67 ± 8.32 x 105 cfu/mL, 3.00 ± 1.00 x 105 cfu/mL and 4.67 ± 3.06 x 105 cfu/mL respectively and Moin moin sample has the highest total coliform count of 6.67 ± 4.93 x 105 cfu/mL. The bacteria isolated from the samples were identified as Enterococcus aerogenes, Proteus vulgaris, Citrobacter freundii, Escherichia coli, Bacillus species, Staphylococcus aureus, Micrococcus luteus and Salmonella enterica. Proteus vulgaris produced the highest zone of inhibition of 15.00 mm with ciprofloxacin while none of the isolates produced a zone of inhibition with rifampicin. It can be concluded from this study that some of the foods sold have considerable number of bacteria which can pose a health risk to the consumers.